A quaternary-ammonium-functionalized covalent organic framework for anion conduction. Issue 33 (2nd May 2017) - Guo, Hongxia; Wang, Junhua; Fang, Qianrong; Zhao, Yun; Gu, Shuang; Zheng, Jie; Yan, Yushan
Abstract : A new anion conducting covalent organic framework (COF) was prepared by covalently tethering quaternary ammonium (QA) ions onto the pore walls of COF 1, 3, 5-triformylphloroglucinol- o -tolidine (TpBD-Me) through bromination and quaternization. Abstract : Here we report a new anion conducting covalent organic framework (COF). Quaternary ammonium (QA) ions are covalently tethered onto the pore walls of COF 1, 3, 5-triformylphloroglucinol- o -tolidine (TpBD-Me) through bromination and quaternization. The QA-functionalized COF shows a bicarbonate conductivity of 5.3 mS cm −1 at 20 °C and 27.0 mS cm −1 at 80 °C, accompanied by 3.3 wt% water uptake and <1.0% swelling ratio at 20 °C. This QA-functionalized COF provides a new option for anion conducting materials.